Analisis Strategi Manajemen Jasa dalam Meningkatkan Kepuasan Pelanggan di PT Gojek Indonesia - Advent Chandra; Felicia Tiffani Kojongian; Mohamad Zein Saleh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the service management strategies implemented by PT Gojek Indonesia to enhance customer satisfaction. Using a qualitative approach based on literature review, the research explores the relationship between service quality, service diversification, and technological innovation in shaping customer experiences. The findings reveal that service management strategies, such as quick booking features, real-time tracking, and digital payment solutions via GoPay, significantly influence customer satisfaction. Service variations like Go-Ride, Go-Car, and Go-Food enable Gojek to meet diverse customer needs, while a focus on reliability and security assurance fosters user loyalty. The study highlights the importance of continuous innovation and quality improvement to maintain Gojek's competitive position in the online transportation service market.